1999
DOI: 10.1046/j.1365-2362.1999.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of heparin‐induced IgG antibody in heparin‐induced thrombocytopenia type II

Abstract: Our results suggest that a very high frequency of heparin-induced IgG in heparin-induced thrombocytopenia type II patients can be detected using a novel antigen assay. The rapid determination of pathogenic heparin-induced IgG may be a useful tool for the rapid diagnosis of heparin-induced thrombocytopenia type II that could facilitate further management of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Whether this finding can also explain the lower incidence of HIT in danaparoid‐treated patients remains to be studied in a larger series of experiments (Magnani, 1993). To date, the lower incidence of HIT in these patients has been attributed to the difference in the chemical structure of danaparoid and the heparins (Magnani, 1993; Greinacher et al , 1994; Chong, 1995) and a lower incidence of the binding of danaparoid to HIT‐IgG in the presence of platelet factor 4 (Wang et al , 1999b). The present data support the literature findings whereby LMW heparins crossreact with HIT antibodies in 100% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this finding can also explain the lower incidence of HIT in danaparoid‐treated patients remains to be studied in a larger series of experiments (Magnani, 1993). To date, the lower incidence of HIT in these patients has been attributed to the difference in the chemical structure of danaparoid and the heparins (Magnani, 1993; Greinacher et al , 1994; Chong, 1995) and a lower incidence of the binding of danaparoid to HIT‐IgG in the presence of platelet factor 4 (Wang et al , 1999b). The present data support the literature findings whereby LMW heparins crossreact with HIT antibodies in 100% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This membrane‐based assay detected IgG antibodies in 73 SRA‐positive HIT sera, in which anti‐PF4–heparin antibody was detected. In a study using an assay based on capture of HIT antibody‐hPF4–heparin by protein A, Wang et al (1999) found HIT IgG in 37 out of 38 HIT sera. In contrast, using ELISA with covalently bound hPF4–heparin to capture HIT antibody, Amiral et al (1996b) failed to detect anti‐hPF4–heparin IgG from 12 HIT sera ( n = 38).…”
Section: Discussionmentioning
confidence: 99%
“…The assay was performed under previously reported experimental conditions. 8 14 C-labeled SRA. The biologic effect of the patient's heparin-induced IgG antibody was determined by using 14 Clabeled SRA.…”
Section: Methodsmentioning
confidence: 99%
“…5 Antigen assays determine antibodies toward the PF4/heparin complex by ELISA, 6 heparin-induced IgG by biotin-labeled PF4, 7 and fluorescence-labeled heparin. 8,9 The sensitivity of all assays ranges from 80% to 98%. Antigenic and biologic assays have been compared in several studies to define the sensitivity and specificity.…”
mentioning
confidence: 99%